2002
DOI: 10.1258/095646202760029750
|View full text |Cite
|
Sign up to set email alerts
|

Is there a need for rescreening of patients treated for genital chlamydial infections?

Abstract: Summary:The present communication reviews reasons to perform rescreening of chlamydia-infected persons. It brings up dif® culties to differentiate between relapse and reinfection. Studies on follow-up of chlamydia-positive cases after therapy are reviewed. It also highlights reasons for therapeutic failure, like compliance, pharmacological factors, including poor bioavailability, wrong dose regimens, lack of adherence to drug intake, neglect of partner noti® cation and concomitant therapy in consorts, possible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 30 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…In the patient with persistent NGU, the treatment failure may have been due to other factors, such as incomplete compliance with the treatment, poor bioavailability, unfavorable pharmacokinetics, or re-infection. 20 Clinical studies with ofloxacin and levofloxacin have shown high eradication rates of C. trachomatis. [21][22][23] In previous studies in which fluoroquinolone-susceptible strains of C. trachomatis were exposed to sub-MICs of fluoroquinolones to select fluoroquinolone-resistant mutants in vitro, resistance did not occur during several serial passages equivalent to a typical treatment period.…”
Section: Discussionmentioning
confidence: 99%
“…In the patient with persistent NGU, the treatment failure may have been due to other factors, such as incomplete compliance with the treatment, poor bioavailability, unfavorable pharmacokinetics, or re-infection. 20 Clinical studies with ofloxacin and levofloxacin have shown high eradication rates of C. trachomatis. [21][22][23] In previous studies in which fluoroquinolone-susceptible strains of C. trachomatis were exposed to sub-MICs of fluoroquinolones to select fluoroquinolone-resistant mutants in vitro, resistance did not occur during several serial passages equivalent to a typical treatment period.…”
Section: Discussionmentioning
confidence: 99%
“…The use of NAATs is endorsed. Most authorities do not recommend a routine test of cure if the patient has been given and complied with appropriate treatment; however, some do [51]. The importance of partner notification and screening is highlighted.…”
Section: Screening For C Trachomatismentioning
confidence: 99%
“…Reason for such non-compliance is yet to be discovered. [23] H. ducreyi showed more resistance than Escherichia coli to antimicrobial peptides. It is also recognized to possess β-lactamase activity making it resistant to the antibiotic ampicillin.…”
Section: Introductionmentioning
confidence: 99%